A Descriptive Profile of Abused Female Sex Workers in India (Journal of Health, Population and Nutrition, 2010)
This descriptive study presents the profiles of abused female sex workers (FSWs) in Chennai, India. Of 100abused FSWs surveyed using a structured questionnaire, severe forms of violence by intimate partners werereported by most (98%) respondents. Of the total sample, 76% experienced violence by clients. Sexualcoercion experiences of the FSWs included verbal threats (77%) and physical force (87%) by intimate partnersand forced unwanted sexual acts (73%) by clients. While 39% of the women consumed alcohol beforemeeting a client, 26% reported that their drunkenness was a trigger for violence by clients. The findingssuggest that there is an urgent need to integrate services, along with public-health interventions amongFSWs to protect them from violence. Recognition of multiple identities of women in the contexts of intimaterelationships versus sex work is vital in helping women to stay safe from adverse effects on health.Key words: Descriptive studies; HIV; Spouse abuse; Violence; Violence against women; IndiaDOI: 10.3329/jhpn.v28i3.5546J HEALTH POPUL NUTR 2010 Jun;28(3):211-220